Prognostic validity of talent orientation in soccer - Hohmann, A.; Siener, M.; He, R. (German Journal of Exercise and Sport Research, 2018)
Several talent-screening programs conducted within elementary schools have implemented motor diagnostics to introduce children to groups of sports including both game and specific sports, the latter of which includes gymnastics, skiing, and tennis. However, as in most other sports, the predictive value for soccer regarding such early testing is unclear. This prospective cohort study evaluated the mid-term prognostic validity of general motor tests as well as a soccer-specific score calculated from a test battery. The sample consisted of N=2965 U9 age group of children from the Fulda Movement Check (FMC). The FMC is a basic check comprised of two anthropometric parameters and eight general items of the German Motor Test 6-18 by Boes and Schlenker with the addition of a ball throw. The test data were collected from the second grade classes of 2011-2014. The soccer competition performance of those children who chose soccer (n=316) up to the end of the season 2016/17 (September 30, 2017) was recorded. This group of U12-U15 players was then assigned individually to four different competition levels. The prognostic validity of the motor tests was determined using analysis of variance, odds ratios, and a discriminant analysis. All diagnostic methods exhibited medium to high prognostic validity over the 2- to 6-year time span from the talent screening and talent orientation period to the later soccer competitions in the early adolescent U12-U15 age groups. The prognostic relevance of the nine general motor tests was confirmed.